The effects of the toxic red tide dinoflagellate Karenia brevis on the survival, growth, and development of the marine gastropod Crepidula fornicata - Clark, Daria. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Biology.; Advisor: Jan Pechenik.; Committee: Sara Lewis, Phil Starks, and Colin Orians.; Keywords: Aquatic sciences, Climate change, and Ecology.